2015
DOI: 10.1155/2015/746917
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant Iodine131Lipiodol after Resection of Hepatocellular Carcinoma

Abstract: Background. Survival after liver resection for HCC is compromised by a high rate of intrahepatic recurrence. Adjuvant treatment with a single, postoperative dose of intra-arterial I131 lipiodol has shown promise, as a means of prolonging disease-free survival (DFS). Methodology. DFS and overall survival (OS) after a single dose of postoperative I131 lipiodol were compared to liver resection alone, for treatment of hepatocellular carcinoma (HCC). Data were collected retrospectively for patients who had a curati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…The IRT included I 131 -mAb, I 131 -lipiodol and I 125 seeds, obviously three strong RCTs provided the benefits for all the internal radiotherapy(Chen et al 2013 ; Lau et al 1999 ; Li et al 2020a ). However, some studies didn’t show any recurrence-free or OS benefit(Chung et al 2013 ; Furtado et al 2015 ).The implantation of internal radioactive source is also technique requirement which might be restriction of the application. The ranking of different treatments according to SUCRA was as follows: TACE + PVC, 88.0%; IRT, 82.3%; ERT, 72.8%; AIT, 71.8%; Huaier, 59.4%; HAIC, 58.7%; TACE, 51.0%, IFN, 48.0%; OCT, 39.0%; CIK, 36.7%; DC, 30.7%; BCAA, 30.5%; NA, 23.4%; SOR, 7.8%.…”
Section: Discussionmentioning
confidence: 99%
“…The IRT included I 131 -mAb, I 131 -lipiodol and I 125 seeds, obviously three strong RCTs provided the benefits for all the internal radiotherapy(Chen et al 2013 ; Lau et al 1999 ; Li et al 2020a ). However, some studies didn’t show any recurrence-free or OS benefit(Chung et al 2013 ; Furtado et al 2015 ).The implantation of internal radioactive source is also technique requirement which might be restriction of the application. The ranking of different treatments according to SUCRA was as follows: TACE + PVC, 88.0%; IRT, 82.3%; ERT, 72.8%; AIT, 71.8%; Huaier, 59.4%; HAIC, 58.7%; TACE, 51.0%, IFN, 48.0%; OCT, 39.0%; CIK, 36.7%; DC, 30.7%; BCAA, 30.5%; NA, 23.4%; SOR, 7.8%.…”
Section: Discussionmentioning
confidence: 99%
“…However, a multicenter RCT involving 103 patients showed that the adjuvant 131I-iodine oil treatment did not improve RFS and OS[ 55 ]. Another retrospective study with the largest sample to date showed no significant survival improvement with the 131I-iodine oil adjuvant therapy[ 56 ]. The results of the meta-analysis showed that intra-arterial instillation of 131I-iodine oil after hepatectomy significantly reduced the risk of HCC recurrence and improved DFS and OS[ 57 , 58 ], but it still needs to be confirmed by multicenter large sample RCTs.…”
Section: Adjunctive Local Treatmentmentioning
confidence: 99%
“… 38 Finally, another promising method seems to be the use of radiolabeled lipiodol, which is a safe radiotracer that leads to tumor necrosis and is associated with Disease-Free Survival (DFS) and OS benefit. 41 Despite the multiple clinical trials of TKIs and ICIs, that are underway, no systematic therapy is considered standard of care in the adjuvant setting.…”
Section: Postoperative Therapymentioning
confidence: 99%